2018
DOI: 10.1002/jmri.26247
|View full text |Cite
|
Sign up to set email alerts
|

Brain abnormalities in myalgic encephalomyelitis/chronic fatigue syndrome: Evaluation by diffusional kurtosis imaging and neurite orientation dispersion and density imaging

Abstract: Background Diffusional kurtosis imaging (DKI) and neurite orientation dispersion and density imaging (NODDI) metrics provide more specific information regarding pathological changes than diffusion tensor imaging (DTI). Purpose To detect microstructural abnormalities in myalgic encephalomyelitis (ME) / chronic fatigue syndrome (CFS) patients by using DKI and NODDI metrics. Study Type Prospective. Population Twenty ME/CFS patients and 23 healthy controls were recruited. Field Strength/Sequence Three‐b value DWI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…A previous DTI study reported increased FA values in the right arcuate fasciculus (Zeineh et al, 2014) and decreased FA values in the genu of the corpus callosum and right anterior limb of the internal capsule in ME/CFS patients (Kimura et al, 2019). Interestingly, we did not find any significant differences in FA that confirm these findings (Kimura et al, 2019; Zeineh et al, 2014) which could be due to the differences in b values and gradient directions (Schilling et al, 2017). It has also been shown that higher b values provides better contrast, greater sensitivity to tissue diffusivity and less T2 shine through (Burdette et al, 2001; DeLano et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A previous DTI study reported increased FA values in the right arcuate fasciculus (Zeineh et al, 2014) and decreased FA values in the genu of the corpus callosum and right anterior limb of the internal capsule in ME/CFS patients (Kimura et al, 2019). Interestingly, we did not find any significant differences in FA that confirm these findings (Kimura et al, 2019; Zeineh et al, 2014) which could be due to the differences in b values and gradient directions (Schilling et al, 2017). It has also been shown that higher b values provides better contrast, greater sensitivity to tissue diffusivity and less T2 shine through (Burdette et al, 2001; DeLano et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…No precise underlying causes of ME/CFS have been identified. Brain imaging has been performed using several MRI techniques to advance our understanding of the pathophysiology of ME/CFS (Barnden et al, 2015; Barnden et al, 2019; Kimura et al, 2019; Thapaliya et al, 2020; Zeineh et al, 2014). Qualitative analysis of structural imaging showed a higher percentage (78%) of abnormal brain scans in ME/CFS patients compared with healthy controls (21%) (de Lange et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A feature found in ME/CFS patients compared to HCs was that there was significantly lower mean kurtosis in the right superior longitudinal fasciculus. This pathway is involved in processes such as emotion, language, attention and memory and could be altered in ME/CFS patients, the study, however, is limited by sample size and the contribution of potential gender bias [79].…”
Section: Discussionmentioning
confidence: 99%
“…80 Abnormal NODDI parameters were also reported in patients with myalgic encephalomyelitis/chronic fatigue syndrome. 81 Billiet and colleagues 82 found reduced ND in the "unidentified bright objects" in neurofibromatosis type 1. Other studies focused on perinatal encephalopathy, 83 SYN1Q555X mutation, 84 C9orf72 disease, 85 and sarcoma survivors.…”
Section: Other Brain Disordersmentioning
confidence: 98%